Selling to major accounts : tools, techniques, and practical solutions for the sales manager - Bacon, Terry R. (American Management Assoc., 1999)
In most businesses, 80% of the revenue comes from 20% of the customers. Management of these key accounts demands discipline, direction, and purpose. Account managers and salespeople must be able to identify and capture key opportunities and use a systematic approach to growing the accounts. Here's where they'll fired the powerful tools, processes, and techniques to succeed. -- Provided by publisher.